2012
DOI: 10.1073/pnas.1205693109
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning gene networks using simple sequence repeats

Abstract: The parameters in a complex synthetic gene network must be extensively tuned before the network functions as designed. Here, we introduce a simple and general approach to rapidly tune gene networks in Escherichia coli using hypermutable simple sequence repeats embedded in the spacer region of the ribosome binding site. By varying repeat length, we generated expression libraries that incrementally and predictably sample gene expression levels over a 1,000-fold range. We demonstrate the utility of the approach b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 46 publications
3
97
0
Order By: Relevance
“…1E). This behavior could be the result of the presence of repeated sequence spacers that increased the distance of the promoter from the structural gene (35). Surprisingly, the sensor construct devoid of any FapR-binding site (n = 0, Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1E). This behavior could be the result of the presence of repeated sequence spacers that increased the distance of the promoter from the structural gene (35). Surprisingly, the sensor construct devoid of any FapR-binding site (n = 0, Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Accumulating evidence from exhaustive genetic studies has already shown that TR variation has dramatic, often backgrounddependent phenotypic effects in model organisms (Verstrepen et al 2005;Kashi and King 2006;Fondon et al 2008;Borel et al 2012;Egbert and Klavins 2012;Morrison et al 2012;RavehSadka et al 2012). In yeasts, TR variation in promoters has been shown to alter gene expression (Vinces et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although new technologies in DNA engineering are ever expanding the number of tuneable 'knobs' in synthetic circuits [52,53], promoter dynamic ranges are particularly flexible in that they can be altered with many techniques, e.g. by random mutagenesis [26], by manipulation of polymerase binding sites [54] or by the addition of sequence repeats [55]. In its current form, our model analysis can also be used to study the effect of tuneable protein half-lives [56], the strength of ribosomal binding sites [27], and in general, other genetic modifications that can be modelled as a linear scaling of protein expression rates.…”
Section: Optimized Designs Non-optimized Designsmentioning
confidence: 99%